Economic appraisal of small-scale solar organic Rankine cycle operating under different electric tariffs and geographical conditions - Tardi, Mohammed (Wiley, 2020)
In the present paper, the economic feasibility of small-scale solar organic Rankine cycle power applications which are assisted with auxiliary gas heaters is investigated. The system is analyzed using three different capacities of ORC system with R-245fa (35, 65, and 110 kWe) in combination with solar water heating system (SWHS) using three models. Flat plate, compound parabolic and evacuated tube solar collectors were used to generate heat with overall heat transfer coefficient (FRUL) of 4.35, 1.57, and 2.23 W/m(2). K respectively. System Advisor Model (SAM) is used to simulate the solar water heater system and optimize the tilt angle, collector area, volume of storage tank and capacity of auxiliary heater under the climatic conditions of Abu Dhabi, New Delhi, Larnaca, Madrid and Munich. The simulation results revealed that the evacuated tube and the compound parabolic collectors performed better than the flat plate collectors. The economic analysis showed that Solar ORC Power Plant is economically and technically feasible with all types of the thermal collectors in Famagusta/Larnaca, Munich and Madrid where the electricity tariff is higher than other cities. Levelized cost of energy (LCOE) is calculated using mathematical model and it ranges between 0.07 and 0.2 USD/kWh based on the plant capacity and type of thermal collectors. Moreover, the profit increase as the plant capacity increase where SIR is 1.05, 1.71, and 2.10 for 35, 65, and 110 kW plant capacity SORC with CPC. A sensitivity analysis is also performed to investigate the effect of operating hours, electricity tariff, ORC unit cost and ORC unit type on the feasibility of the system. According to the results, the electricity tariff and operating hours are the most important parameters because they have a large effect and Play important role on the economic feasibility of the system.
Keywords: economic feasibility; organic Rankine cycle; solar ORC; thermal collector